Method for bonding components with reduced penetration deformation
By using pumpable thermal foam filler compositions in the automotive industry, the optimization problem of BLRT phenomenon is solved, better adhesive flexibility and contact quality is achieved, automobile vibration and noise are reduced, and bonding is significantly improved Line penetration problem.
Patent Information
- Application Number
- CN202380041874.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-06
- Filing Date
- 2023-06-28
- Publication Date
- 2024-12-20
AI Technical Summary
The existing bond wire penetration (BLRT) phenomenon in the automotive industry is aggravated with the tendency of lightweight and thinning of metal plates, making it difficult to optimize the deformation problem of the adhesive composition during thermal expansion, affecting automotive vibration and noise reduction. Small effect.
Using a pumpable hot foam filler composition, the composition is foamed by applying the composition on the first substrate and placing the second substrate within a certain distance, and then heating to the foaming agent activation temperature to form Adhesive to reduce BLRT phenomenon. The composition comprises rubber, polyvinyl chloride or acrylic resin, foaming agent and liquid epoxy resin, preferably partially crosslinked rubber and plasticizer.
It significantly improves BLRT performance, reduces bond wire penetration, improves the flexibility and contact quality of the adhesive, enhances the stability and adhesion performance under heat treatment conditions, and effectively reduces automotive vibration and noise.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to a method for bonding substrates, particularly in the automotive industry, or white goods articles using a pumpable thermally foamable filler composition. Background Art
[0002] Manufactured products often contain hollow components that result from the manufacturing process and / or are designed into the product for various purposes (e.g., weight reduction). For example, a motor vehicle includes several such hollow components throughout the vehicle, including in the roof, hood, trunk lid, and doors of the vehicle. It is often desirable to additionally connect / bond the components / substrates forming the hollow components at least in certain locations in order to minimize vibrations caused when the vehicle moves and the noise generated by such vibrations.
[0003] Suitable compositions for joining these parts / substrates to reduce vibrations are capable of expanding their volume upon application of heat in order to increase their flexibility and reduce variations in the surface of the bonded parts, also known as "read-through", for aesthetic reasons. For example, during the manufacture of a vehicle, the hollow portion of the vehicle roof may contain a strip of uncured composition applied between the roof beam and the top layer of the vehicle. These strips are applied with sufficient thickness to ensure a firm and direct contact of the applied uncured composition with the roof beam and the top layer of the vehicle. This application at specific locations allows a large area to be covered with the electrocoat liquid, while the strip of applied uncured composition is already inserted between the upper and lower top layers, and subsequently during the heat treatment step, the expandable composition expands and firmly connects the two layers to minimize the vibrations caused when the vehicle moves and the noise caused by such vibrations.
[0004] The specific material properties of the cured adhesive composition are crucial for the bond line penetration (BLRT) phenomenon. Adhesive BLRT is a visible deformation of the substrate on the cured adhesive bond line. The deformation is mainly the result of the difference in the coefficient of thermal expansion between the substrate and the adhesive. With the trend of lightweighting in (for example) the automotive industry, thinner and thinner metal sheets are used for automobile manufacturing. With the reduction of steel thickness and bending stiffness, the BLRT effect caused by the composition occurs more frequently. Therefore, the adhesive composition optimized by BLRT receives more and more attention.
[0005] WO2020048905A1 describes a rubber composition with improved BLRT performance, which comprises at least one solid rubber, a processing oil, a vulcanization system, a filler and a foaming agent. However, the BLRT performance still has the potential for improvement.
[0006] It would therefore be desirable to provide a method of bonding substrates using a thermally expandable composition that is advantageous in terms of improved BLRT performance. SUMMARY OF THE INVENTION
[0007] It is an object of the present invention to provide a method for bonding substrates with a thermally expandable composition which provides reduced BLRT phenomena.
[0008] Surprisingly, the present invention provides a solution to this problem by providing a method for bonding two substrates, the method comprising the following sequential steps:
[0009] -i) applying a pumpable heat-foamable filler composition onto a first substrate S1, and
[0010] -ii) placing the second substrate S2 so that the distance between the first substrate S1 and the second substrate S2 at the application location of the pumpable heat-foamable filler composition is 2-10 mm, and
[0011] -iii) heating the first substrate S1 and the second substrate S2 to a temperature above the activation temperature of the blowing agent to foam the pumpable heat-foamable filler composition, wherein between step ii) and step iii), the applied pumpable heat-foamable filler composition is not in contact with the second substrate S2, and wherein the pumpable heat-foamable filler composition comprises:
[0012] - at least one rubber, preferably a synthetic rubber, more preferably a partially crosslinked synthetic rubber and more preferably a diene rubber, in an amount preferably ranging from 1% to 20% by weight, preferably from 3% to 15% by weight and more preferably from 5% to 10% by weight relative to the total weight of the composition;
[0013] - polyvinyl chloride resin and / or acrylic resin powder, preferably polyvinyl chloride resin; preferably 5 to 40 wt %, 8 to 30 wt %, preferably 10 to 20 wt %, based on the total weight of the pumpable thermally foamable filler composition;
[0014] - Blowing agent, preferably 1 to 10 wt %, 2 to 8 wt %, preferably 3 to 6 wt %, based on the total weight of the pumpable thermally foamable filler composition.
[0015] The method according to the invention is particularly suitable for sound attenuation / vibration reduction, for example in automotive applications. Further aspects of the invention are subject matter of further independent claims. Preferred embodiments of the invention are subject matter of the dependent claims. DETAILED DESCRIPTION OF THE INVENTION
[0017] If not otherwise stated, the unit term "wt%" refers to the weight percentage based on the weight of the corresponding total composition. The terms "weight" and "mass" are used interchangeably herein.
[0018] The volume change of the thermally expandable material is determined using the DIN EN ISO 1183 density measurement method (Archimedes principle) in deionized water in combination with the sample mass determined by means of a precision balance.
[0019] The pumpable thermal foamable filler composition preferably contains a liquid epoxy resin. A liquid epoxy resin is a material that is liquid or at least flowable at ambient temperature (23° C.). Polyepoxides known to those skilled in the art as “reactive diluents” are also referred to herein as liquid epoxy resins.
[0020] Suitable liquid epoxy resins for use in the compositions of the present invention include liquid resins of formula (I)
[0021]
[0022] wherein R' and R" are each independently a hydrogen atom or a methyl group, and s has an average value of 0 to 1. Preference is given to those liquid resins of formula (I) wherein the subscript s has an average value of less than 0.2.
[0023] The liquid epoxy resin of formula (I) is a diglycidyl ether of bisphenol A, bisphenol F and bisphenol A / F, wherein A represents acetone and F represents formaldehyde, which are used as reactants for preparing these bisphenols. Therefore, the bisphenol A liquid resin has a methyl group, the bisphenol F liquid resin has a hydrogen atom, and the bisphenol A / F liquid resin has a methyl group and a hydrogen atom as R' and R'' in formula (I). In the case of bisphenol F, positional isomers may also exist, especially those derived from 2,4'- and 2,2'-hydroxyphenylmethane.
[0024] Such liquid epoxy resins are commercially available, for example, as Araldite® GY 204, Araldite® GY 250, Araldite® GY 260, Araldite® GY 281, Araldite® GY 282, Araldite® GY 285, Araldite® PY 304, Araldite® PY 720 (from Huntsman); DER®330, DER®331, DER®332, DER®336, DER®354, DER®351, DER®352, DER®356 (from Dow); Epikote®162, Epikote®827, Epikote®828, Epikote®158, Epikote®862, Epikote®169, Epikote®144, Epikote®238, Epikote®232, Epikote®235 (from Hexion), Epalloy®7190, Epalloy®8220, Epalloy®8230, Epalloy®7138, Epalloy®7170, Epalloy®9237-70 (from CVC), Chem Res®E 20, Chem Res®E 30 (from Cognis), Beckopox®EP 116. Beckopox® EP 140 (from Cytec), Epiclon EXA-4850 (from Sun Chemical).
[0025] Other suitable liquid epoxy resins are glycidyl products of dihydroxybenzene derivatives such as resorcinol, hydroquinone and catechol; furthermore bisphenols or polyphenols, for example bis(4-hydroxy-3-methylphenyl)methane, 2,2-bis(4-hydroxy-3-methylphenyl)propane (bisphenol C), bis(3,5-dimethyl-4-hydroxyphenyl)methane, 2,2-bis(3,5-dimethyl-4-hydroxy-phenyl)propane, 2,2-bis(3,5-dibromo-4-hydroxy-phenyl)propane, 2,2-bis(4-hydroxy-3-tert-butyl- phenyl) propane, 2,2-bis(4-hydroxyphenyl) butane (bisphenol B), 3,3-bis(4-hydroxyphenyl) pentane, 3,4-bis(4-hydroxyphenyl) hexane, 4,4-bis(4-hydroxyphenyl)-heptane, 2,4-bis(4-hydroxyphenyl)-2-methylbutane, 2,4-bis(3,5-dimethyl-4-hydroxyphenyl)-2-methylbutane, 1,1-bis(4-hydroxyphenyl) cyclohexane (bisphenol Z), 1,1-bis(4-hydroxyphenyl)-3,3,5-trimethylcyclohexane (bisphenol TMC), 1,1-bis(4-hydroxyphenyl)-1-phenyl-ethane, 1,4-bis[2-(4-hydroxyphenyl)-2-propyl]benzene)(bisphenol P), 1,3-bis[2-(4-hydroxyphenyl)-2-propyl]benzene)(bisphenol M), 4,4'-dihydroxybiphenyl (DOD), 4,4'-dihydroxybenzophenone, bis(2-hydroxynaphthalene-1-yl)methane, bis(4-hydroxynaphthalene-1-yl)methane, 1,5-dihydroxynaphthalene, tris(4-hydroxyphenyl)methane, 1,1,2,2-tetrakis(4-hydroxyphenyl)ethane, Bis(4-hydroxyphenyl)ether, bis(4-hydroxyphenyl)sulfone; condensation products of phenol with formaldehyde obtained under acidic conditions, such as phenol novolac or cresol novolac; aromatic amines, such as aniline, toluidine, 4-aminophenol, 4,4'-methylenediphenyldiamine (MDA), 4,4'-methylenediphenyldi(N-methyl)amine, 4,4'-[1,4-phenylenebis(1-methylethylidene)]dianiline (dianiline P), 4,4'-[1,3-phenylenebis(1-methylethylidene)]dianiline (dianiline M).
[0026] In another embodiment, the liquid epoxy resin is an aliphatic or alicyclic polyepoxide, such as diglycidyl ether; glycidyl ether of a saturated or unsaturated, branched or unbranched, cyclic or open-chain C2 to C3 diol (e.g., ethylene glycol, propylene glycol, butanediol, hexanediol, octanediol, polypropylene glycol, dimethylolcyclohexane, neopentyl glycol); a trifunctional or tetrafunctional, saturated or unsaturated, branched or unbranched, cyclic or open-chain polyol such as castor oil; Glycidyl ethers of sesame oil, trimethylolpropane, trimethylolethane, pentaerythritol, sorbitol or glycerol and alkoxylated glycerol or alkoxylated trimethylolpropane; hydrogenated bisphenol A, F or A / F liquid resins, or glycidyl products of hydrogenated bisphenol A, F or A / F; N-glycidyl derivatives of amides or heterocyclic nitrogen bases, such as triglycidyl cyanurate and triglycidyl isocyanurate, and reaction products of epichlorohydrin and hydantoin.
[0027] Aliphatic or cycloaliphatic liquid epoxy resins are commercially available, for example, as Araldite® DY-C, Araldite® DY-F, Araldite® DY-H, Araldite® DY-T, Araldite® DY 0397, Araldite® DY 3601 (from Huntsman), DER® 732, DER® 736 (from Dow); Heloxy® BD, Heloxy® HD, Heloxy® TP, Epikote® 877 (from Hexion), Beckopox® EP 075 (from Cytec). It is also possible to use mixtures of aliphatic or cycloaliphatic polyepoxides of formula (I) and aromatic epoxides, in particular mixtures of diglycidyl ethers of bisphenol A, bisphenol F and bisphenol A / F and diglycidyl ethers of α,ω-alkanediols, wherein the α,ω-alkanediols preferably contain 2 to 10 carbon atoms. Such a mixture is commercially available, for example, as DER 358 from Dow.
[0028] In another embodiment, the liquid epoxy resin is a polyepoxide prepared by oxidation of olefins, such as vinylcyclohexene, dicyclopentadiene, cyclohexadiene, cyclododecadiene, cyclododecatriene, isoprene, 1,5-hexadiene, butadiene, polybutadiene, or divinylbenzene.
[0029] The liquid epoxy resin is preferably a liquid resin of formula (I) as described above, more preferably a variant thereof as described above as preferred.
[0030] In the context of the present application, particularly preferred liquid epoxy resins are epoxy resins based on bisphenol A diglycidyl ether with an epoxy equivalent weight of 156-250 g / eq, such as DER® 331 from Dow.
[0031] The liquid epoxy resin is preferably contained in the composition in an amount of 5-40 wt %, based on the total weight of the composition. In yet another preferred embodiment, the liquid epoxy resin is incorporated into the composition in an amount of 8-30 wt %, 10-25 wt % and in particular 12.5-20 wt %.
[0032] The pumpable heat-foamable filler composition of the present invention contains polyvinyl chloride resin and / or acrylic resin powder as mandatory ingredients.
[0033] As shown in the comparison of Ex. 1 and Ref. 2 in Table 2, the absence of polyvinyl chloride resin and / or acrylic resin powder results in insufficient expansion behavior and an unfavorable open-cell structure.
[0034] The polyvinyl chloride (PVC) resin in the composition of the present application may be a polyvinyl chloride homopolymer or copolymer, preferably a polyvinyl chloride copolymer. If the polyvinyl chloride is a copolymer, it preferably contains a vinyl ester such as vinyl acetate or vinyl propionate as a comonomer of vinyl chloride. The amount of the comonomer is preferably 1-25%, more typically 2-20%, 2-15%, 2-10%, and most preferably 3-7%, relative to the total weight of the copolymer.
[0035] In the context of the present application, a suitable PVC homopolymer is Formolon KVH from Formosa. In the context of the present application, a particularly suitable PVC copolymer is Formolon F 40, also from Formosa.
[0036] The acrylic resin powder that can be used instead of or in combination with the polyvinyl chloride resin is not particularly limited except that it is preferably solid at ambient temperature (23° C.). More preferably, the acrylic resin powder has a glass transition temperature Tg in the range of 50° C. to 120° C., even more preferably in the range of 70° C. to 90° C. The glass transition temperature is determined by DSC. In addition, it is preferred that the acrylic resin powder is capable of forming a plastisol.
[0037] The acrylic resin in the acrylic resin powder may be a homopolymer or a copolymer. Preferred acrylic resins are methyl methacrylate based resins, such as those available as Dianal LP-3106 or Dianal LP-3202 from Dianal America Inc. Another commercially available acrylic resin that can be advantageously used in the present application is KaneAce U 506 from Kaneka.
[0038] One or more polyvinyl chloride resins and / or one or more acrylic resin powders are suitably included in the composition in an amount ranging from 5 to 40 wt%, preferably in an amount of 8 to 30 wt% and most preferably in an amount of 10 to 20 wt%.
[0039] As another mandatory ingredient, the pumpable thermally foamable filler composition of the present invention contains a blowing agent. As a blowing agent for the present invention, any substance can be used as long as it decomposes by heating to generate a gas. Preferably, the blowing agent is a chemical blowing agent. More preferably, the blowing agent is selected from azo compounds, nitroso compounds and hydrazine derivatives, more preferably selected from azo-dicarbonamide, N,N-dinitrosopentamethylenetetramine and diphenylsulfone-3,3'-disulfonylhydrazide. These blowing agents can be used in one or in a mixture of two or more. In the context of the present application, dicyandiamide is particularly preferred as at least a part of the blowing agent because its degradation product (ammonia) can help the liquid epoxy resin to cure and crosslink.
[0040] The amount of the blowing agent in the pumpable heat-foamable filler composition of the present invention is generally in the range of 1 wt % to 10 wt %, 2 wt % to 8 wt %, and preferably in the range of 3 wt % to 6 wt %.
[0041] The feature "pumpable" of the heat-foamed filler composition of the present application is understood to mean that the filler has a viscosity suitable for pumping at ambient temperature (20°C), and preferably has a pasty viscosity. When measured by a rheometer (MCR 301, Anton Paar) with a heatable plate (gap 1000 µm, measuring plate diameter: 25 mm (plate / plate), deformation 0.01-10% at 10 Hz, temperature: 45°C), the viscosity of the pumpable heat-foamed filler composition is preferably in the range of 50-500 Pa.s, and preferably in the range of 150-400 Pa.s. When the viscosity is lower than 50 Pa.s, dripping is more likely to occur, and the shape cannot be fully maintained during processing. On the other hand, if the viscosity exceeds 500 Pa.s, the processability of the material is greatly reduced.
[0042] As a further mandatory component, the pumpable heat-foamed filler composition of the present invention comprises rubber, in particular synthetic rubber, and preferably partially crosslinked synthetic rubber. Exemplarily, the partially crosslinked rubber used in the filler composition of the present invention is preferably a partially crosslinked diene rubber, more preferably selected from acrylonitrile-isoprene copolymer rubber (NIR), acrylonitrile-butadiene copolymer rubber (NBR), styrene-butadiene copolymer rubber (SBR), butadiene rubber (BR) and isoprene rubber (IR). Crosslinking can be the result of adding a crosslinking agent (e.g. divinylbenzene or sulfur). The addition of rubber provides the advantages of improved rheological properties, anti-sagging, anti-washing and higher volume expansion of the resulting filler composition.
[0043] The rubber is generally incorporated into the filler composition of the invention in an amount ranging from 1% to 20% by weight, preferably from 3% to 15% by weight, more preferably from 5% to 10% by weight, relative to the total weight of the composition.
[0044] In addition to the above ingredients, the pumpable heat-foamable filler composition may contain additional ingredients.
[0045] Another ingredient that can be advantageously used in the pumpable heat-foamable filler composition of the present application is a plasticizer. Therefore, the pumpable heat-foamable filler composition of the present application preferably comprises at least one plasticizer. The combination of a low viscosity plasticizer and PVC and / or acrylic resin powder is conducive to a stable pasty state and is conducive to providing good physical strength and good expansion rate to the cured material, especially after humid storage.
[0046] As the plasticizer, any substance can be used as long as polyvinyl chloride can swell and dissolve therein. Mentioned as plasticizers are, for example, phthalates such as di(2-ethylhexyl)phthalate, butyl benzyl phthalate, dinonyl phthalate, diisononyl phthalate (DIDP), diisodecyl phthalate (DIDP), diundecyl phthalate, ditridecyl phthalate (DTDP), diheptyl phthalate and butyl phthaloyl butyl glycolate; aliphatic dibasic acid esters such as dioctyl adipate, didecyl adipate and dioctyl sebacate; polyethylene glycol benzoates such as polyoxyethylene glycol dibenzoate and polyoxypropylene glycol dibenzoate; phosphates such as tributyl phosphate and tricresyl phosphate; hydrocarbons such as alkyl-substituted biphenyls, alkyl-substituted terphenyls, partially hydrogenated terphenyls, aromatic process oils and pile oils. These plasticizers can be used alone or as a mixture of two or more thereof. In the context of the present application, preferred among the abovementioned plasticizers are phthalates, in particular diisononyl phthalate (DINP), ditridecyl phthalate (DTDP) and diisodecyl phthalate (DIDP).
[0047] In the context of the present application, suitable amounts of plasticizer are 5 to 40 wt%, preferably 10-30 wt%, 15-25 wt% and in particular 10-20 wt%, relative to the total weight of the composition.
[0048] The pumpable thermal foaming filler composition of the present application preferably also contains a curing agent for the liquid epoxy resin. As a curing agent, a latent curing agent is preferably used, which provides curing by heating and can be activated at a temperature of 80-250°C. Specific examples of latent curing agents include dicyandiamide, 4,4'-diaminodiphenyl sulfone, imidazole derivatives such as 2-N-heptadecyl imidazole, isophthalic acid dihydrazide, N,N-dialkyl urea derivatives, N,N-dialkyl thiourea derivatives and melamine derivatives. These curing agents can be used independently or as a mixture of two or more of them, depending on the curing conditions and their properties. A particularly preferred curing agent used in the context of the present application is dicyandiamide. In a preferred embodiment, dicyandiamide is used as the only epoxy curing agent in the composition because it is observed that the combination of liquid epoxy resin and dicyandiamide provides a very stable mixture during storage.
[0049] The amount of curing agent is preferably in the range of 0.05 to 2.0 wt%, 0.1 to 1.5 wt%, 0.2 to 1.2 wt%, 0.4 to 1.0 wt%, more preferably in the range of 0.5 to 0.8 wt%, relative to the total weight of the composition. It has been observed that the combination of a high content of liquid epoxy resin with a small amount of curing agent provides a material that crosslinks to a suitable degree once cured and provides good adhesion properties on oiled metal substrates. In addition, the system also provides good physical strength.
[0050] In addition to the above-mentioned ingredients, the pumpable thermally foamable filler composition of the present application further preferably comprises a filler, in particular an inorganic filler. Suitable inorganic fillers are, for example, calcium carbonate, silicon dioxide, clay and fly ash. These inorganic fillers can be used alone or as a mixture of two or more thereof. More than one modified form of filler can also be used, for example different modified forms of calcium carbonate.
[0051] In the context of the present application, the amount of filler, in particular inorganic filler, is not particularly limited and depends on the viscosity of the composition without filler (i.e., a lower viscosity allows the incorporation of more filler, while a higher viscosity without filler allows only a small amount of filler to be incorporated), while keeping the composition pumpable. Therefore, the amount of filler is generally in the range of 10-55% by weight, preferably 15-45% by weight and more preferably 20-35% by weight relative to the total weight of the composition.
[0052] The pumpable heat-foamable filler composition of the present application may contain appropriate amounts of other additives as needed, for example, thixotropy imparting agents such as organic bentonite, fumed silica, castor oil derivatives, pigments such as carbon black, titanium dioxide, zinc dioxide or other inorganic pigments, dehydrating agents such as calcium oxide and powdered silica gel and / or PVC stabilizers.
[0053] The amount of these additional additives is not particularly limited, however, the content is preferably not more than 15% by weight, more preferably 10% by weight or less, even more preferably 8% by weight or less.
[0054] In a particularly preferred embodiment of the present application, the pumpable heat-foamable filler composition of the present application comprises:
[0055] - 8 to 30% by weight, 10 to 25% by weight, preferably 12.5 to 20% by weight of a liquid epoxy resin, preferably a liquid resin of formula (I);
[0056] 5 to 40% by weight, 8 to 30% by weight, preferably 10 to 20% by weight of polyvinyl chloride resin and / or acrylic resin powder, preferably polyvinyl chloride resin;
[0057] 1 to 20% by weight, 3 to 15% by weight, preferably 5 to 10% by weight of rubber, preferably synthetic rubber, more preferably diene rubber;
[0058] - 1 to 10% by weight, 2 to 8% by weight, preferably 3 to 6% by weight of a blowing agent;
[0059] - 5 to 40% by weight, 10 to 30% by weight, 15 to 25% by weight, preferably 10 to 20% by weight of plasticizers, preferably phthalates;
[0060] - 0.05 to 2.0 wt. %, 0.1 to 1.5 wt. %, 0.2 to 1.2 wt. %, 0.4 to 1.0 wt. %, preferably - 0.5 to 0.8 wt. % of a curing agent, preferably a latent curing agent;
[0061] 10% to 55%, 15% to 45%, preferably 20% to 35% by weight of fillers, preferably inorganic fillers.
[0062] The above weight % is based on the total weight of the composition.
[0063] The pumpable heat-foamable filler composition of the present invention can be prepared by mixing the above ingredients with a mixer. The type of the mixer used is not particularly limited and includes, for example, various mixers such as a planetary mixer and a kneader.
[0064] The method for bonding two substrates comprises the following sequence of steps:
[0065] -i) applying a pumpable heat-foamable filler composition onto a first substrate S1, and
[0066] -ii) placing the second substrate S2 so that the distance between the first substrate S1 and the second substrate S2 at the application location of the pumpable heat-foamable filler composition is 2-10 mm, and
[0067] -iii) heating the first substrate S1 and the second substrate S2 to a temperature higher than the activation temperature of the blowing agent to foam the pumpable heat-foamable filler composition. During the time between the performance of step ii and the start of step iii), the applied pumpable heat-foamable filler composition is not in contact with the second substrate S2. During this time period, the applied pumpable heat-foamable filler composition is preferably in its unfoamed state.
[0068] As shown in the comparison of Ex.1 and Ref.1 in Table 1, the applied pumpable thermally foamable filler composition Ex.1 not in contact with the second substrate S2 after S2 positioning resulted in improved bond line penetration compared to the prior art composition and Ex.1 applied in contact with the second substrate S2 after S2 positioning. It was further surprisingly found that the lap shear strength was comparable between the two application methods of composition Ex.1.
[0069] Advantageously, in step i), the pumpable heat-foamable filler composition is applied in the form of a strip having a width of 3-18 mm, preferably 6-12 mm, more preferably 10-12 mm.
[0070] It is further advantageous that in step i), the pumpable heat-foamable filler composition is applied in the form of a bead having a height of 1-8 mm, preferably 1-4 mm, more preferably 1.5-3 mm, most preferably 1.5-2.5 mm.
[0071] It is also advantageous if, in step i), the pumpable heat-foamable filler composition is applied in the form of a strip having a length of 10 mm to 2 m, preferably a length of 2 cm to 10 cm or a length of 0.5 m to 3 m. The first is advantageous if the composition is applied in the form of a dotted strip, for example for bonding a vehicle hood. The latter is advantageous if the composition is applied continuously over a long distance, for example for bonding a vehicle roof.
[0072] Preferably, in step i), the pumpable heat-foamable filler composition is applied in the form of a rectangular strip. Preferably, the ratio of the width to the height of the rectangular strip is 2-10, preferably 3-8, more preferably 5-8.
[0073] It has also been found to be advantageous if the pumpable heat-foamable filler composition is applied in step i) in the form of a bead and the ratio between the distance DI between the first substrate S1 and the second substrate S2 at the location where the pumpable heat-foamable filler composition is applied and the height HT of the bead (DI / HT) is >1-6.5, preferably 1.2-4.5, most preferably 1.5-2.75. This is advantageous in terms of the contact quality with the upper substrate, as shown by the comparison of different height / distance ratios in Table 4. The contact quality leads to better corrosion resistance, adhesion on the substrate and vibration damping.
[0074] In a preferred method, in step i), the pumpable heat-foamable filler composition is applied in the form of a rectangular strip, the height HT of the strip is 1.0-3.5 mm, preferably 1.5-2.5 mm, and the distance DI between the first substrate S1 and the second substrate S2 at the application position of the pumpable heat-foamable filler composition is 3-6 mm, preferably 4-5 mm.
[0075] The first substrate S1 and / or the second substrate S2 are preferably metal substrates, more preferably oiled metal substrates. However, if appropriate, heat-resistant plastics are also conceivable. The first substrate S1 and the second substrate S2 can be made of the same or different materials.
[0076] Preferred metal substrates are those used, for example, in the construction of means of transport, for example in the automotive industry, or in the production of white goods. The process according to the invention is therefore particularly suitable for bonding metal substrates for the production of means of transport, in particular cars, buses, trucks, rail vehicles, ships or aircraft, or white goods, in particular washing machines, tumble dryers or dishwashers, or parts thereof, preferably motor vehicles or components thereof that can be mounted thereon.
[0077] Most preferably, the first substrate S1 is a supporting frame of a vehicle hood, trunk or door or a crossbar of a roof, and the second substrate S2 is a vehicle hood, trunk or door panel or a roof panel.
[0078] Preferably, the metal substrates are oiled substrates, meaning that they are covered with an anti-corrosion oil known to the person skilled in the art. An example of such an anti-corrosion oil is Anticorit PL 3802-39S.
[0079] Preferred examples of the metal substrate are metal substrates selected from steel, aluminum and magnesium, in particular selected from electrolytically galvanized steel, hot-dip galvanized steel, Bonazinc-coated steel, subsequently phosphated steel, aluminum, magnesium and magnesium alloys.Preferred substrates are oiled substrates.
[0080] In step (a) of the method according to the invention, a pumpable heat-foamable filler composition is applied to the first substrate S1. This is carried out, for example, at an application temperature of the pumpable heat-foamable filler composition of 10° C. to 80° C., preferably 25° C. to 50° C., more preferably 30° C. to 40° C. The application is preferably carried out in the form of a bead. Preferably, the application is automatic.
[0081] The pumpable hot-foamable filler composition can be applied over the entire surface or on a portion of the surface of the first substrate S1 facing the second substrate S2. In a preferred application, the pumpable hot-foamable filler composition is applied only on a portion of the substrate surface of the first substrate S1 facing the second substrate S2, preferably less than 20%, less than 10%, less than 5%, preferably less than 2%, especially if the first substrate S1 is a support frame of a vehicle hood, trunk or door.
[0082] In the following step ii), the second substrate S2 is placed so that the distance between the first substrate S1 and the second substrate S2 at the application position of the pumpable heat-foamable filler composition is 2-10 mm. Preferably, after placement, the first substrate S1 and the second substrate S2 are fixed in place, preferably with a mechanical fixing device, preferably mechanical clamping, more preferably mechanical clamping, and then spot welding or laser welding, so that the distance between the first substrate S1 and the second substrate S2, preferably at the position where the pumpable heat-foamable filler composition is applied on the first substrate S1, does not change before step iii) is completed.
[0083] After step ii), the first substrate S1 and the second substrate S2 are heated to a temperature above the activation temperature of the blowing agent to foam the pumpable heat-foamable filler composition, wherein between step ii and step iii), the applied pumpable heat-foamable filler composition is not in contact with the second substrate S2.
[0084] In order to heat and preferably cure the pumpable heat-foamable filler composition in step iii), the pumpable heat-foamable filler composition is preferably heated to a temperature of 150-220° C., preferably 160-200° C., preferably 170-190° C., most preferably 180° C. The heating can be carried out, for example, by infrared radiation or induction heating or in an oven, such as a cathode electrophoresis oven. In this way, an adhesive bond to the pumpable heat-foamable filler composition is obtained.
[0085] Preferably, the duration of the heating step is 10-60 minutes, preferably 10-40 minutes, 10-30 minutes, most preferably 10-20 minutes.
[0086] Preferably, after step iii), the pumpable heat-foamable filler composition is foamed and cured and forms an adhesive bond between the first substrate S1 and the second substrate S2 by direct contact with the two substrates.
[0087] The pumpable heat-foamable filler composition in the adhesive bond can be cured in one step, but curing in two or more steps is also possible, in which case intermediate operating steps between or during the curing steps are possible, such as washing and / or dipping operations of the substrate, such as cathodic electrocoating operations, followed by washing.
[0088] Another aspect of the invention is an article obtainable by the process, in particular a construction of a means of transport, in particular in the automotive industry, or a white goods article, most preferably selected from the group consisting of a roof, a hood, a trunk lid and a door.
[0089] The present invention is further explained in the following Experimental Section, which, however, should not be construed as limiting the scope of the present invention. Example
[0090] A reference heat-expandable rubber composition (Ref. 1) identical to composition E15 from WO2020048905A1 was prepared and compared with the pumpable heat-foamable filler composition Ex. 1 of the invention described below.
[0091] For the formulations of the pumpable thermal foamable filler compositions Ex.1-Ex.3 and the reference formulations Ref.2- Ref.3, each component was compounded according to the compounding amounts shown in Table 1. The premix of Ex.1 contained 12.9 wt% of styrene-butadiene rubber, 26.8 wt% of DIDP plasticizer, 39.9 wt% of calcium carbonate filler, and 20.4 wt% of liquid epoxy resin (based on bisphenol A / epichlorohydrin, epoxy equivalent of 180-190 g / equivalent). Ex.2- Ex.3 and Ref.2- Ref.3 were adjusted by keeping the same weight ratio between the premix components as in the premix of Ex.1.
[0092] Table 1, all amounts are by weight
[0093] Determination of expansion rate
[0094] The volume increases in Table 3 were determined using the DIN EN ISO 1183 density measurement method (Archimedes principle) in deionized water in combination with the sample mass determined by a precision balance.
[0095] Determination of penetration
[0096] The compositions Ref.1 and Ex.1 were applied as a single bead (50 mm long, rectangular profile, 6 mm wide, height as described in Table 2) in the center of the test specimen (steel EG (DC06+ZE 75 / 75), thickness 0.25 mm, 150 × 105 mm). The specimen was then fixed in a special frame and a thin steel plate (DC01 C590 0.25 mm) painted on one side only was placed on top of the other specimen (the unpainted side was wetted by the composition to which the bead was applied) at a distance of 4.5 mm (using a Teflon® spacer). The two metal plates were fixed at the outer edges by screwing the frame segments together. The specimen was then placed in an oven at 200°C for 20 minutes. After cooling to 23°C, the upper side of the sample (white coated metal plate surface) was analyzed with a deflectometer. The entire sample was placed in the deflectometer chamber and the white coated steel surface was illuminated with a periodic pattern of parallel white and black lines. A camera recorded the pattern reflected by the white metal plate surface. Through computational post-processing of the data (filtering and curve extraction), potential deformations can be visualized.
[0097] The obtained curvature profiles were then compared with the results obtained by using a strip consisting of a commercially available prior art product as a reference (SIKASEAL-710LS (Sika Germany)). Compositions with similar or slightly better curvature profiles than those obtained with the reference composition in terms of BLRT performance were marked as "4" (similar, curvature visible) or "3" (curvature slightly reduced), respectively. Compositions with significantly improved curvature profiles (little or no significant bond line penetration could be detected) compared to those obtained with the reference example were marked as grades "2" or "1", respectively. The results are shown in Table 2.
[0098] Determination of substrate contact quality
[0099] In Table 4, a similar setup as described above for determining penetration was used to determine the quality of contact of the expanded composition with the upper side ("upper substrate") placed on top of the first sample ("base substrate") containing the applied composition.
[0100] For all determinations, composition Ex.1 was applied as a single strip (50 mm long, rectangular profile, 12 mm wide, height as described in Table 4) to the center of a first specimen (“base substrate”, steel EG (DC06+ZE 75 / 75), thickness 0.25 mm, 150×105 mm). The specimen was then fixed in a special frame and a second specimen (“upper substrate”, steel EG (DC06+ZE 75 / 75), thickness 0.25 mm, 150×105 mm) was placed on top of the first specimen at a distance as indicated in Table 4 (using Teflon® spacers, “Thickness spacer (mm)”). The two metal sheets were fixed at the outer edges by screwing the frame segments together. The test specimens were then placed in an oven at 200°C for 20 minutes. After cooling to 23°C, the dimensions of the contact area of the expanded composition with the upper substrate and with the substrate were compared. The following rating system was applied:
[0101] ++ = contact area of the base substrate with contact area of the upper substrate ≥ 100%
[0102] + = Contact area with upper substrate < 100%-85% of contact area with base substrate
[0103] + / - = Contact area with upper substrate < 85%-70% of contact area with base substrate
[0104] Tensile strength (TS) (DIN ISO 527)
[0105] Curing conditions: 15 minutes at 180°C target temperature.
[0106] The tensile strength was determined in accordance with DIN ISO 527 on a tensile machine at a tensile speed of 10 mm / min using the 3-fold determination method.
[0107] Lap shear strength (LSS) (DIN EN 1465)
[0108] Steel test pieces (thickness 0.8 mm) cleaned and subsequently oiled with Anticorit PL 3802-39S were bonded to the composition on a 25 × 20 mm bonding surface using a Teflon pad with a layer thickness of 2.0 mm for Ref.1 and Ex.1 and cured. As previously described, an additional sample was made for Ex.1 (right outer column in Table 2), also using a Teflon pad with a thickness of 2.0 mm, but the applied adhesive strip was only 1.0 mm thick, so that the applied composition Ex.1 did not come into contact with the upper steel piece before curing.
[0109] Curing conditions: 15 minutes at 180°C target temperature.
[0110] The lap shear strength was determined in accordance with DIN EN 1465 on a tensile machine at a tensile speed of 10 mm / min using the 3-fold method.
[0111] Table 2
[0112] Table 3
[0113] Table 4, bc = before curing, ac = after curing.
Claims
1. A method for bonding two substrates, comprising the following steps in the following order: -i) applying a pumpable heat-foamable filler composition onto a first substrate S1, and -ii) placing the second substrate S2 so that the distance between the first substrate S1 and the second substrate S2 at the application location of the pumpable heat-foamable filler composition is 2-10 mm, and -iii) heating the first substrate S1 and the second substrate S2 to a temperature above the activation temperature of the blowing agent to foam the pumpable heat-foamable filler composition, wherein between step ii) and step iii), the applied pumpable heat-foamable filler composition is not in contact with the second substrate S2, and wherein the pumpable heat-foamable filler composition comprises: - at least one rubber, preferably a synthetic rubber, more preferably a partially crosslinked synthetic rubber and more preferably a diene rubber, in an amount preferably ranging from 1% to 20% by weight, preferably from 3% to 15% by weight and more preferably from 5% to 10% by weight relative to the total weight of the composition; - polyvinyl chloride resin and / or acrylic resin powder, preferably polyvinyl chloride resin; preferably 5 to 40 wt %, 8 to 30 wt %, preferably 10 to 20 wt %, based on the total weight of the pumpable thermally foamable filler composition; - Blowing agent, preferably 1 to 10 wt %, 2 to 8 wt %, preferably 3 to 6 wt %, based on the total weight of the pumpable thermally foamable filler composition.
2. The method of claim 1, characterized in that In step i), the pumpable heat-foamable filler composition is applied in the form of a strip having a width of 3-18 mm, preferably 6-12 mm, more preferably 10-12 mm.
3. The method according to any one of the preceding claims, characterized in that In step i), the pumpable heat-foamable filler composition is applied in the form of a bead having a height of 1-8 mm, preferably 1-4 mm, more preferably 1.5-3 mm, most preferably 1.5-2.5 mm.
4. The method according to any one of the preceding claims, characterized in that In step i), the pumpable heat-foamable filler composition is applied in the form of a strip having a length of 10 mm to 2 m, preferably a length of 2 cm to 10 cm or a length of 0.5 m to 3 m.
5. The method according to any one of the preceding claims, characterized in that In step i), the pumpable heat-foamable filler composition is applied in the form of a rectangular strip, preferably, the ratio of the width to the height of the rectangular strip is 2-10, preferably 3-8, more preferably 5-8.
6. The method according to any one of the preceding claims, characterized in that In step i), the pumpable heat-foamable filler composition is applied in the form of a bead, and in step ii), the ratio (DI / HT) between the distance DI between the first substrate S1 and the second substrate S2 at the application position of the pumpable heat-foamable filler composition and the height HT of the bead is >1-6.5, preferably 1.2-4.5, most preferably 1.5-2.
75.
7. The method according to any one of the preceding claims, characterized in that In step i), the pumpable heat-foamable filler composition is applied in the form of a rectangular strip, and at the application position of the pumpable heat-foamable filler composition, the height HT of the strip is 1.0-3.5 mm, preferably 1.5-2.5 mm, and the distance DI between the first substrate S1 and the second substrate S2 is 3-6 mm, preferably 4-5 mm.
8. The method according to any one of the preceding claims, characterized in that Based on the total weight of the pumpable thermally foamable filler composition, the amount of polyvinyl chloride resin and / or acrylic resin powder, preferably polyvinyl chloride resin, is 5 to 40 wt %, preferably 8 to 30 wt %, more preferably 10 to 20 wt %.
9. The method according to any one of the preceding claims, characterized in that The first substrate S1 is a supporting frame of a vehicle hood or a crossbar of a vehicle roof, and the second substrate S2 is a vehicle hood panel or a vehicle roof panel.
10. The method according to any one of the preceding claims, characterized in that The pumpable heat-foamable filler composition further comprises a liquid epoxy resin, and the amount of the liquid epoxy resin is preferably 8 wt % to 30 wt %, 10 wt % to 25 wt %, preferably 12.5 wt % to 20 wt %, based on the total weight of the pumpable heat-foamable filler composition.
11. The method according to claim 10, characterized in that The pumpable heat-foamable filler composition further comprises a curing agent for the liquid epoxy resin, preferably a latent curing agent, more preferably dicyandiamide, and the amount of the curing agent is preferably in the range of 0.05 wt % to 2.0 wt %, 0.1 wt % to 1.5 wt %, 0.2 wt % to 1.2 wt %, 0.4 wt % to 1.0 wt %, more preferably in the range of 0.5 wt % to 0.8 wt %, based on the total weight of the pumpable heat-foamable filler composition.
12. The method according to any one of the preceding claims, characterized in that The blowing agent is a chemical blowing agent, more preferably, the blowing agent is selected from azo compounds, nitroso compounds and hydrazine derivatives, more preferably selected from azodicarbonamide, N,N-dinitrosopentamethylenetetramine and diphenylsulfone-3,3'-disulfonylhydrazide.
13. An article obtained by the process according to claim 1 to claim 12, in particular a construction of a means of transport, in particular in the automotive industry, or a white goods article, most preferably selected from the group consisting of a roof, a hood, a trunk lid and a door.
